Soil variability in a toposequence of the Monzón Valley, high jungle of Peru: Morphology, properties and classification - Lagos-Damas, Rodrigo F. (2025)
Knowing the taxonomy, mineralogy, and properties of soils is essential to understand their genesis, functionality, and potential use, and it is fundamental for implementing land-use planning and to characterize soil use management systems. The objective of this study was to describe and correlate the taxonomic characteristics (Soil Taxonomy and World Soil Classification), morphological, physicochemical, and mineralogical characteristics of soils in relation to their physiographic position, based on 15 profiles of a toposequence obtaining 81 horizons. It was verified that soil variability was linked to relief; likewise, soil orders ranging from Entisols to Inceptisols were identified according to the Soil Taxonomy classification. While through the World Soil classification, the groups: Fluvisols, Regosols, Umbrisols, Cambisols, and Luvisols were identified. Morphologically, the fluvial soils were characterized by presenting Ap surface horizons, verifying the absence of subsurface horizons, denoting that they are young soils. In the physical attributes, there were sandy textures in fluvial soils and clayey textures in residual soils. Greater fertility was evidenced in lower terraces, and as the relief rises, fertility decreases. There was a correlation between physical and chemical attributes; in this sense, fertility depends to some extent on physical characteristics. The mineralogical analysis, using X-ray diffraction and X-ray fluorescence, revealed a predominance of 2:1 minerals in fluvial soils, associated with SiO₂/R₂O₃ molar ratios > 2; whereas in residual soils, 1:1 minerals predominated, with ratios < 2. Finally, fertility decreased according to soil origin: highest in fluvial soils, intermediate in alluvial soils, and lowest in residual soils.